Some Subsyndromal Psychiatric Symptoms And Executive Functions Performance In Association With Subjective Memory Problems Among A Final Year Medical Students In Mansoura University (Journal of Pharmaceutical Negative Results, 2023)
Background Subjective memory complaints (SMC) are commonly reported by older people and often prompt concerns about the possibility of cognitive impairment expressed by patients, carers and clinicians. Aim and objectives This study aimed to explore the executive functions of a final year medical students with subjective memory problems in Mansoura University. Explore the association between executive functions obtained and the severity of psychiatric symptoms among medical students with subjective memory problems. Subjects and methods This study has been conducted in Mansoura Faculty of Medicine, Mansoura Psychiatry Department, through two years from June 2020 to 2022. It was a cross sectional study with analytical component, 382 students applied for the inclusion criteria. Results prevalence of executive function deficits among students with subjective memory problems as well as, it demonstrates that 28.8% have concern about verbal fluency , only 18.6% of total number of response on stroop-test were >40 , 2errors are detected among 8.4% of the students. Conclusion It has been stated that young doctors should be given the same care and support that we expect them to provide to their patients. The same should be extended to medical students in order to promote resilience and personal fulfilment, and for enhancement of professionalism and patient care.